A hero's guide to deadly dragons : the heroic misadventures of Hiccup the Viking as told to Cressida Cowell - Cowell, Cressida (Cowell, Cressida. How to train your dragon, 2010)
It's Hiccup's birthday, but he must save his dragon, Toothless, from being banished. He sneaks into the Meathead Public Library to steal the Vikings' sacred book, but must brave the Hairy Scary Librarian, the army of Meathead Warriors, and the Driller Dragons.